1981
DOI: 10.1002/oms.1210161004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal surface ionization of some complex salts

Abstract: Thermal ionization on the surface of a heated wire is applied to the volatilization products of alkali salts of carboxylic and sulfonic acids, and to quaternary ammonium salts. The mass spectra of the alkali salts exhibit almost exclusively cationized molecules. They provide evidence for the evaporation of intact clustered molecules even under conditions of a slow rate of evaporation of the salts. The method appears to be of interest for selective detection of alkali salts from complex mixtures. With the ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Recently, Hillenkamp proposed four possible ion formation mechanisms for laser mass spectrometry: (1) thermal evaporation of ions from the solid; (2) thermal evaporation of neutral molecules from the solid, followed by ionization in the gas phase; (3) "true" laser desorption; and (4) ion formation in a laser-generated plasma (15). The two thermal processes have been confirmed for nonlaser radiative heating of organic salts (16,17) and cationization of thermally evaporated neutrals (17)(18)(19). The detection of similar species in laser mass spectrometry implies that such thermal processes may occur in LMS (20).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, Hillenkamp proposed four possible ion formation mechanisms for laser mass spectrometry: (1) thermal evaporation of ions from the solid; (2) thermal evaporation of neutral molecules from the solid, followed by ionization in the gas phase; (3) "true" laser desorption; and (4) ion formation in a laser-generated plasma (15). The two thermal processes have been confirmed for nonlaser radiative heating of organic salts (16,17) and cationization of thermally evaporated neutrals (17)(18)(19). The detection of similar species in laser mass spectrometry implies that such thermal processes may occur in LMS (20).…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies of quaternary ammonium salts by field desorption (FD),14 electrohydrodynamic ionization (EHD),' secondary ion mass spectrometry (SIMS),".' 2s2Cf plasma desorption (PD); laser desorption (LD),8,9 fast atom bombardment (FAB) ,Io in-beam chemical ionization thermal d e s o r p t i~n , '~,~~ in-beam E1 and thermal surface ionization (TSI), 18,19 proved not only the possibilities of analysis of intact quaternary ammonium ions in the gas phase, but also demonstrated the possibility of achieving volatilization of quaternary ammonium salt molecules. It has been stated that producing ions under desorption conditions is opposite to the situation under E1 and CI conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They point to different ion formation processes: 1. The formation of the CH3C02Na2 + ions can be attributed to the decomposition of dimers or higher clusters on the K+ ion emitting hot silica gel surface [30]. It was found that this ion forming reaction gives rise to a more abundant ion signal with heated metal than with silica gel surfaces.…”
Section: Acids and Saltsmentioning
confidence: 99%
“…With alkali salts of some acids it was found that [M +Alkali] + ions are formed by decomposition of clustered neutral salt molecules on surfaces having temperatures above 1300 K [30]. This mechanism should also contribute to the formation of quasimolecular ions of salts in LD MS.…”
Section: Introductionmentioning
confidence: 99%